Pulmonary delivery of excipient-free tobramycin DPIs for the treatment of Pseudomonas aeruginosa lung infection with CF - Cheng, Song; Huang, Haozhou; Zhang, Zhihao; Chen, Mateng; Zhang, Yulong; Lin, Mengxing; Yang, Gang; Kanye, Lynda Thubelihle; Zhang, Qingzhen; Xue, Ning; Shi, Kaiqi; Dong, Bin; et al. (Frontiers in Pharmacology, 2025)
Pseudomonas aeruginosa infection has become a widespread problem in patients with cystic fibrosis (CF). A safe and effective manufacturing method is required to produce antibiotic dry powder inhalations (DPIs) which can be effectively delivered to treat lung infections. In this study, an excipient-free tobramycin inhalable powder was prepared using spray freeze-drying (SFD) method. The mass median aerodynamic diameters (MMAD) of optimized inhalable powder prepared by SFD was 1.30 µm, and the fine particle fractions (FPF) reached 83.31%. In both in vitro and in vivo safety and activity studies, the inhalable powder showed excellent safety performance at both animal and cellular levels, with a minimum inhibitory concentration (MIC) of 0.5 μg/mL. Compared with intravenous injection, inhalation of excipient-free tobramycin inhalable powder had a better effect in the infected mouse model because of its amorphous state. This study demonstrates that excipient-free tobramycin inhalable powder with good delivery and deposition performance can be successfully obtained using the SFD method. Inhalation of excipient-free tobramycin inhalable powder has the potential to be a promising strategy for treating pulmonary infections caused by P. aeruginosa in patients with CF.